A virtual resiliency program for lymphoma survivors: helping survivors cope with post-treatment challenges. Issue 11 (2nd November 2021) - Perez, Giselle K.; Walsh, Emily A.; Quain, Kit; Abramson, Jeremy S.; Park, Elyse R.
Abstract: Objectives To adapt and test the feasibility, acceptability, and preliminary efficacy of an 8-week resiliency group program for posttreatment lymphoma survivors. Design and outcomes . This is an exploratory mixed methods study. Phase 1: We conducted qualitative interviews to inform program adaptation. Phase 2: Using a single-arm pilot design, we assessed program feasibility, acceptability, and preliminary efficacy (exploratory outcomes: stress coping, uncertainty intolerance, distress). We also examined the feasibility of collecting hair cortisol samples. Results . Phase 1: Survivors reported feeling socially isolated as they grappled with lingering symptoms that interfered with their return to normalcy. Fears about recurrence triggered bodily hypervigilance. Survivors desired wellness programs that 1) target their whole-body experience, 2) promote social connectedness, and 3) manage fear of recurrence. Phase 2: Thirty-seven survivors enrolled. Participants completed a median of 7/8 sessions, and 76.9% completed ≥6/8 sessions; 65% provided a hair sample. Survivors demonstrated improvements in stress coping (d = .67), uncertainty tolerance (d = .71), and anxiety (d = .41) at program completion. Conclusions . Findings suggest promising feasibility and efficacy of this program in addressing posttreatment survivorship challenges, particularly fears of uncertainty. A cancer care model that adopts early integration of this program posttreatment has the potential to improve survivors' emotional, social and physical well-being.